DEVELOPMENT OF PARTIALLY HYDROLYSED AND DEODOURISED FISH FLOUR. - SETTY, T. M RUDRA; SUDHAKARA, N S; NAGARAJ, A S; CHETTY, H P (Fishery Technology, 2017)
A process developed for preparation of partially hydrolysedand deodouriscd (PHD) fish flour, without solvent extraction isdescribed. The PHD fish flour prepared from four varietiesof trash fish, had creamy white colour and contained 87-92%protein and 7-8% available lysine. The products had shelf lifeof more than an year at room temperature, and caused nogrittiness when incorporated in snacks and bakery products at10% and 7.5% level respectively. The flour prepared fromNemipterus spp. had a PER 2.32 compared to 2.68 of raw fishmeat and 2.5 of standard casein.